2022
DOI: 10.1002/advs.202200491
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Disrupt the IGFBP2/mTOR/PTEN Axis to Inhibit Ovarian Cancer Growth

Abstract: By exploiting the self‐therapeutic properties of gold nanoparticles (GNPs) a molecular axis that promotes the growth of high‐grade serous ovarian cancer (HGSOC), one of the deadliest gynecologic malignancies with poorly understood underlying molecular mechanisms, has been identified. The biodistribution and toxicity of GNPs administered by intravenous or intraperitoneal injection, both as a single dose or by repeated dosing over two weeks are first assessed; no biochemical or histological toxicity to vital org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
7
2
Order By: Relevance
“…We found that IGF2BP3 could regulate the expression of key DAMP-related genes. Besides, we found that expression of IGFBP2 negatively correlated with OS in PCPG patients, which was consistent with previous studies which also identified IGFBP2 as an oncogene in various tumor types [ 95 , 96 , 97 ]. Altogether, these indicated that insulin-like growth factor binding protein family played an important role in the ICD tumor process.…”
Section: Discussionsupporting
confidence: 92%
“…We found that IGF2BP3 could regulate the expression of key DAMP-related genes. Besides, we found that expression of IGFBP2 negatively correlated with OS in PCPG patients, which was consistent with previous studies which also identified IGFBP2 as an oncogene in various tumor types [ 95 , 96 , 97 ]. Altogether, these indicated that insulin-like growth factor binding protein family played an important role in the ICD tumor process.…”
Section: Discussionsupporting
confidence: 92%
“…injection (100–300 μg per mouse) in either an acute setting (24 h and single injection of GNP) or a chronic setting (GNP injections every 2 days for 14 days). Importantly, biochemical and immunohistochemical analyses revealed the absence of toxicity . In the present study, three doses of GNP treatment did not appreciably reduce the tumor size.…”
Section: Resultscontrasting
confidence: 48%
“…Cell proliferation was measured by cell counting by the trypan blue method as described previously . Nearly 60–80% inhibition of proliferation in all the cancer cell lines tested was seen following GNP treatment when compared with nontreated controls (Figure c).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations